COMPARATIVE STUDY OF THE MANAGEMENT OF VANAME SHRIMP (LITOPENAEUS VANNAMEI) BASED ON DEMOGRAPHIC FACTORS AT MOLANG BEACH TULUNGAGUNG - Firda Ama Zulfia; Ika Airin Nur Rohmadhani; Nova Yesika Gultom; Sueb Sueb (UNEJ e-Proceeding, 2016)
Sea has benefits to conncet islands in Indonesia, which is one of the natural resources that is very potential to be empowered and can be used as one of the basic capitals of national development. The purpose of this study was to determine the correlation between strategy of management vaname shrimp (Litopenaeus vannamei) and respondents’ ages, to know the difference of strategy of management vaname shrimp (Litopenaeus vannamei) based on respondents’ genders, and to know the difference of strategy of management of vaname shrimp (Litopenaeus vannamei) based on respondents' education levels at Molang Beach Tulungagung. Demographic factors used are ages, genders, and education levels to determine the management strategy of vaname shrimp fishermen at Molang Beach Tulungagung. Molang Beach at Tulungagung was choosen as the research object because it has long beach line and it is managed and used as farming land. The results are the respondents’ ages have a correlation with the strategy that used to manage vaname shrimp, strategy of management vaname shrimp (Litopenaeus vannamei) differs based on genders, and strategy of management vaname shrimp (Litopenaeus vannamei) differs based on levels of education at Molang Beach Tulungagung.